From good to great / Mohd Zamrin Dimon. - Dimon, Mohd Zamrin (Universiti Teknologi MARA Cawangan Selangor, 2019)
It is indeed a pleasure and an honour for me to pen this editorial as I embark on this journey as the new Editorin-Chief for the Journal of Health and Clinical Sciences, the official journal for the Faculty of Medicine Universiti Teknologi MARA (UiTM). I would like to express my gratitude and appreciation to all the members of the Editorial Board for initiating and subsequently driving this journal to its current position. I am pleased that the journal has met its planned timeline in achieving the due recognition and rise to greater heights in the new future. As the official journal of the faculty, it has an important role in supporting the faculty to achieve its goal as a Centre of Excellence in medicine.